PENGARUH SUSTAINABILITY REPORTING TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Situmorang, Dion; Bimo, Irenius Dwinanto (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2023)
This study aimed to analyse the effect of sustainability reporting on firm value by considering audit quality as a moderating variable. The sample selection used the purposive sampling method, with the main criteria being companies that publish sustainability reporting separately and from 2016 to 2019, respectively. The number of samples is 27 companies, with the number of observations from 2016 to 2019 as many as 108 companies. Hypothesis testing is done by panel data regression using views. The test results show that sustainability reporting positively affects firm value. In the moderation model, empirical evidence shows that audit quality moderates the effect of sustainability reporting on firm value. The results of this study imply that for companies, management needs to disclose sustainable aspects in quality because it is a consideration for investors to invest. For investors, the company's contribution to sustainable elements can be reflected in the sustainability reporting prepared by the company.